The Role of Social Media in Electoral Propaganda of the 19th House of Representatives (2020) from the Point of View of the Jordanian Voter - Olaimat, Farhan; Alhammad, Khalaf Lafee; Yahya Al-Hadeed , Ali (Dirasat: Human and Social Sciences, 2022)
This study aimed at recognizing the role of social media in electoral propaganda of the 19th House of Representatives from the point of view of Jordanian voter. This study is considered as a descriptive study that based on survey method through the tool of questionnaire on a sample consists of (520) individuals from the Jordanian voters and it has reached a lot of findings of which the most important are the followings: It has been illustrated that 82.3% of the study sample use social media sites permanently. It has been explained that 41.5% of the study sample will practice its constitutional right to elect the 19th House of Representatives. 70% of the study sample saw that electoral propaganda of the 19th House of Representatives candidates was effective an useful. It has been shown that Facebook is the most follow-up by the Jordanian voter of the electoral propaganda of the 19th House of Representatives candidates. It has been illustrated that social, and economic topics that published by the candidates of the 19th House of Representatives via social media sites are the most important to be interested in by the study sample. It has been explained that more than a half of the study sample prefers the electoral propaganda of the 19th House of Representatives candidates via social media webs instead of electoral campaigns.